Die Macht des Definierens Eine diskurslinguistische Typologie am Beispiel des Burnout-Phänomens - Schnedermann, Theresa (Sprache und Wissen (SuW), 2021)
How is it that a definition of a phenomenon like "burnout" can assert itself in spite of academic criticism? This book pursues this question by modelling the embeddedness of discursive practices of definition within academic culture and society and their increasing power. By taking a discourse-linguistic and praxeological approach, this book opens up new perspectives for the (linguistic) research into definition.